Assessing the effectiveness of interactive grammar-based teaching in enhancing EFL learners’ concord comprehension and learning confidence - Handayani, Nengah Dwi; Wardana, I Ketut (Universitas Islam Negeri Palangka Raya, Indonesia, 2025)
Despite various grammar teaching strategies implemented since elementary school, many university students struggle with English concord, resulting in low English proficiency. This study aimed to examine the impact of interactive grammar-based teaching (IGBT) on students’ understanding of English concord and to investigate the correlation between concord comprehension and self-confidence. Using a one-group pretest-posttest design, 20 students participated in a seven-week English concord course, attending weekly 120-minute sessions. Grammar tests and a self-confidence questionnaire were administered to assess students' comprehension and perception of concord. Data analysis included descriptive statistics, paired t-tests, and correlation analysis to evaluate grammar proficiency and confidence levels. The results revealed a significant decrease in concord errors, from 46.5% to 33.25%, indicating an improvement in comprehension from 53.5% to 66.75%. The intervention had a significant impact on students' understanding of concord (Sig. 0.000 < 0.05) and a positive impact on their self-confidence (Sig. 0.000 < 0.05). Key errors identified included overgeneralization, misuse of morphological markers, and insufficient contextual understanding. This study concludes that IGBT enhances EFL students’ grammatical accuracy and self-confidence, highlighting the necessity for interactive grammar teaching strategies. Future research should examine IGBT’s impact on a larger, more diverse student population.